Evaluatıon On The Candıda Colonızatıon On The Surface Of Orthodontıc Brackets And The Adhesıon Of The Straıns To Buccal Epıthelıal Cells - Gülin Paçal-Yeşilbağ; Zahir Altuğ; Ayşe Kalkancı (Galenos Yayinevi, 2003)
Many types and numbers of microorganisms may be colonized in the oral cavity. Candida albicans is the most frequently isolated fungal species which colonizes oral mucosal cells. Denture protheses play an important role by increasing the risk of colonization. Sixty children, who do not have any systemic disease, who were not treated with orthodontic appliances before were investigated. In this study, Candida colonization and adhesion rates have been investigated among 60 children who treated with orthodontic brackets (mean age: 17, 8 years) and 15 (%25) of them were found to be colonized by candida species (13 C. Albicans, 1C. kefyr, 1C. lusitaniae). Fourteen of 15 subjects (%93.3) were between 16-18 years old. All the isolates were exposed with buccal epithelial cells in-vitro, and the adhesion rate was found to be %12. The adhesion activity was detected only in C. albicans strains.